2010
DOI: 10.1002/ejoc.201001196
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive DFT Study on Site‐, Regio‐, and Stereoselectivity of Diels–Alder Reactions Leading to 5‐Hydroxybenzofurans

Abstract: Diels–Alder reactions between the substituted furans 1a–1c and Danishefsky's diene (2), yielding 5‐hydroxybenzofurans, were studied by density functional theory [B3LYP/6‐31G(d) level] in benzene as solvent (SP/CPCM). The mechanistic details of these reactions, especially with respect to regio‐, site‐, and stereochemistry were analyzed in detail. Moreover, the extrusion of nitrous acid from the Diels–Alder cycloadducts and the formation of the aromatic products were also explained in order to give a total descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…2 In continuation of our previous computational studies concerning Diels-Alder reactions of nitro-substituted furans and thiophenes here we want to present the results of the analogous reaction of 2-nitro-1-tosylpyrrole 2c with Danischefsky's diene 5. [3][4][5] Experimentally, the sole product found in this reaction is 5-hydroxy-1-tosylindole (Scheme 1).…”
Section: Introductionmentioning
confidence: 94%
“…2 In continuation of our previous computational studies concerning Diels-Alder reactions of nitro-substituted furans and thiophenes here we want to present the results of the analogous reaction of 2-nitro-1-tosylpyrrole 2c with Danischefsky's diene 5. [3][4][5] Experimentally, the sole product found in this reaction is 5-hydroxy-1-tosylindole (Scheme 1).…”
Section: Introductionmentioning
confidence: 94%
“…For comparable DA reactions using nitropyrroles [6a], nitroselenophenes [6b] and nitrofurans [6c] with substituted 1,3-butadienes, it was experimentally demonstrated that the nitrated cycloadducts suffered cis-extrusion of the nitro group as nitrous acid and subsequent aromatization. Moreover, the mechanism for the reactions involving nitrofurans was fully characterized using DFT methods and it was shown that the elimination step, leading to stable elimination products (DG Ã reac $ À22kcal mol À1 at B3LYP/ 6-31(G)d level, relative to the reactive pair), was the responsible factor for the feasibility of the overall process [68]. Therefore, in an analogous manner to the reactions involving nitropyrroles, nitroselenophenes and nitrofurans under thermal conditions, elimination of HNO 2 from the DA cycloadducts and conversion of the elimination products into benzo [b]thiophene derivatives contribute to the overall domino processes (Scheme 3) that are initialized by nucleophilic attacks of electron-rich dienes to the electron-deficient dienophiles in polar DA reactions, with two-stage one-step mechanisms [66].…”
Section: Experimental Verificationmentioning
confidence: 99%